Students’ Difficulties in Learning Listening at the Eleventh Grade Students of SMAN 3 Praya - Nurul Wahidah; I Made Sujana; Ni Wayan Mira Susanti; Arifuddin Arifuddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Listening is one of the important language skills in learning English because it is a receptive skill that provides language input for students. However, in reality students still experience many difficulties when learning listening, as well as the eleventh grade students of SMAN 3 Praya. This research was aimed to find out students’ achievement in learning listening at the eleventh grade students of SMAN 3 Praya, to find out the difficulties experienced by students in learning listening and to find out the factors that cause these difficulties. This research used descriptive qualitative method. Out of 121 eleventh grade students, only 44 students were selected as a sample using a simple random technique. The data were collected through test, questionnaire and interview. The results of this study showed that students’ achievement in listening is very poor. Students’ difficulties in listening such as: unfamiliar words, complexities of grammatical structures, long spoken materials, unfamiliar topics, listening without repetition, the way speakers pronounces words, unable to quickly remember words or phrases they had just heard, the speed and accents of the speakers, focus of the students, environmental noises, and quality of recorded material. Then, the factors that cause these difficulties are lack of students practicing listening, students’ lack of vocabulary mastery, students’ lack of motivation, and noisy environment.